1996
DOI: 10.1016/s0035-9203(96)90258-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum: increased proportion of severe resistance (RII and RIII) to chloroquine and high rate of resistance to sulfadoxine-pyrimethamine in peninsular Malaysia after two decades

Abstract: Uncomplicated falciparum malaria patients were randomly assigned to receive either 25 mg/kg chloroquine (CHL) over 3 d or a statim dose of 25 mg/kg sulfadoxine (SDX) plus 1.25 mg/kg pyrimethamine (PYR). Patients were followed up for 28 d and the parasite response graded according to World Health Organization criteria. Overall resistance to CHL was 63.3% and 47.4% to SDX/PYR. RI, RII and RIII rates were 9.1%, 42.4% and 12.1% for CHL and 10.5%, 21.1% and 15.8% for SDX/PYR, respectively. Degree and rates of resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
14
0
2
Order By: Relevance
“…A large-scale study on the clinical efficacy of P. falciparum malaria to SDX/PYR in Peninsular Malaysia conducted in mid 1990s, reported 47% of the study isolates were resistant to SDX/PYR [8]. A subsequent molecular study reported 87% of P. falciparum had triple mutations in pfdhfr and all isolates having point mutation at codon A437G of pfdhps as indication of drug pressure, accompanied by 81% point mutation at codon A581G indicating reduced in vitro responsiveness of SDX [4].…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale study on the clinical efficacy of P. falciparum malaria to SDX/PYR in Peninsular Malaysia conducted in mid 1990s, reported 47% of the study isolates were resistant to SDX/PYR [8]. A subsequent molecular study reported 87% of P. falciparum had triple mutations in pfdhfr and all isolates having point mutation at codon A437G of pfdhps as indication of drug pressure, accompanied by 81% point mutation at codon A581G indicating reduced in vitro responsiveness of SDX [4].…”
Section: Introductionmentioning
confidence: 99%
“…A previous in vivo study followed by a molecular detection of resistance markers has been conducted in Sarawak and showed that CQ resistance occurred widely and therefore, CQ was replaced by sulphadoxine/pyrimethamine (SDX/PYR), and later by artemisinin combination therapy, as the drug of choice for treating uncomplicated falciparum malaria infections in East Malaysia [15]. In West Malaysia, CQ is still used as the first-line drug in the treatment policy of uncomplicated malaria caused by P. falciparum , although a previous in vivo study reported a CQ resistance rate of 63.6% among uncomplicated falciparum malaria patients [16]. Data on the molecular markers of CQ resistance in Peninsular Malaysia is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to chloroquine, an effective and safe anti-malarial that formed the first line of treatment, emerged more than 30 years ago [1], and since then malaria parasites have developed resistance against most of the widely used anti-malarials, including sulfadoxine-pyrimethamine [2,3], mefloquine [4] and quinine [5]. Indeed, it is now generally believed that the widespread use of a new drug will inevitably be followed by the appearance of resistance in the parasite population.…”
Section: Introductionmentioning
confidence: 99%